'Do you think this is normal?': risk, temporality, and the management of children's food allergies through online support groups. (19th May 2021) - Jurich, Ebru Kayaalp
Abstract : Through an online ethnographic analysis of a Facebook allergy group in Turkey, this article investigates how mothers carry out the daily process of managing risks and making decisions relating to the diets of babies with food allergies. Where allergy-management advice provided clinically by doctors tends to take the form of a relatively uniform and future-oriented risk-management process, parents making dietary decisions for babies with food allergies often need immediate advice that doctors cannot provide. To meet this need, many mothers complement the advice they receive from doctors with the knowledge and expertise of strangers online in making decisions about their children's diet. Through a focus on how mothers engage with issues of allergy-related risk in an online community, this study demonstrates the different layers of temporality mothers navigate and the different strategies they employ in responding to allergy-related risk and how these co-exist, often complementarily, with the clinical management of allergies.